A Maneuvering Target Tracking Algorithm Based on the Interacting Multiple Models - Liu Yan-Chang; Zuo Xian-Gang (Institute of Advanced Engineering and Science, 2013)
In view of the limitation of the traditional Kalman filter with which the tracking has big calculation amount and low tracking precision base on the model of CV or CA movement, a algorithm is suggested in the present article which is the Interacting Multiple Models Kalman filter(IMM-KF) with the CV and CA model. Under keeping invariant of the tracking precision of linear motion, This method can make the tracking precision of curve motion approach the linear motion’s. The system simulation results show that this algorithm improved the tracking precision of system with the IMM-KF. DOI: http://dx.doi.org/10.11591/telkomnika.v11i7.2851